Rekomendasi Dan Perbaikan Proses Bisnis Menggunakan Business Process Improvement Pada PT. Trivia Nusantara - Satrio Dwiartono; Nanang Yudi Setiawan; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Trivia Nusantara is stationary supplier, advertising, and printing company. On the daily business, PT. Trivia Nusantara found out that many processes are done incorrectly, the indication are order processing takes a lot of time to be done and the amount of inventory record does not match with the amount of item in the warehouse. Based on those indication, this research aims to evaluate business process and analyze potential problem that may occur and to address the root cause of identified problem on the business process. The first step is analyzing business process using value chain to identify the main process and the secondary process, also to model the identified process using Business Process and Model Notation (BPMN). The next step is analyzing the potential problem and its effect to the company's business process using Failure Mode and Effect Analysis (FMEA). Next step is identifying the root cause of the highest rank from each of the company's business processes using 5-Whys analysis method. From 13 problems identified, there are 7 activities that cannot be solved with Business Process Improvement (BPI) method because the root cause of the problems are human resource. Business process improvement solves 6 activities on menerima order process and menerima barang datang process using streamlining tools on Business Process Improvement (BPI) method. The results of business process improvement are time improvement of 83.77% or 9 minutes 33 seconds per process on penerimaan order process and 1.65% or 33 seconds per process on penerimaan barang process.